Mediated Online Awareness Among Adolescents With and Without ADHD: Using the Occupational Performance Experience Analysis (OPEA). - Fisher, Orit; Berger, Itai; Grossman, Ephraim S.; Maeir, Adina (OTJR: Occupational Therapy Journal of Research, 2023)
Online awareness is essential to learning from one's experiences, enabling adaptive self-management, often challenged among adolescents with attention-deficit hyperactivity disorder (ADHD). This study used an online awareness tool, the Occupational Performance Experience Analysis (OPEA), to examine (a) the online awareness of occupational performance of adolescents with ADHD and controls and (b) the potential modifiability of online awareness after a brief mediation redirecting attention to task demands and contextual factors. Seventy adolescents with and without ADHD were administered the OPEA after completing cognitive assessments. The OPEA comprises a verbal description of experiences, scored for representation of main actions, temporal context, and coherence, completed again after mediation. Results point to significantly less coherent descriptions of occupational performance among adolescents with ADHD compared with adolescents without ADHD; modifiability was only examined in the ADHD group and demonstrated significantly more coherent descriptions after mediation. Findings may elucidate online awareness of occupational performance as an occupational therapy intervention target for adolescents with ADHD.